Influence of Audiovisual Training on Horizontal Sound Localization and Its Related ERP Response - Cai, Yuexin; Chen, Guisheng; Zhong, Xiaoli; Yu, Guangzheng; Mo, Hanjie; Jiang, Jiajia; Chen, Xiaoting; Zhao, Fei; Zheng, Yiqing (Frontiers in Human Neuroscience, 2018)
The objective was to investigate the influence of audiovisual training on horizontal sound localization and the underlying neurological mechanisms using a combination of psychoacoustic and electrophysiological (i.e., event-related potential, ERP) measurements on sound localization. Audiovisual stimuli were used in the training group, whilst the control group was trained using auditory stimuli only. Training sessions were undertaken once per day for three consecutive days. Sound localization accuracy was evaluated daily after training, using psychoacoustic tests. ERP responses were measured on the first and last day of tasks. Sound localization was significantly improved in the audiovisual training group when compared to the control group. Moreover, a significantly greater reduction in front-back confusion ratio for both trained and untrained angles was found between pre- and post-test in the audiovisual training group. ERP measurement showed a decrease in N1 amplitude and an increase in P2 amplitude in both groups. However, changes in late components were only found in the audiovisual training group, with an increase in P400 amplitude and decrease in N500 amplitude. These results suggest that the interactive effect of audiovisual localization training is likely to be mediated at a relatively late cognitive processing stage.